Analysis of the Factors Affecting Individual Taxpayers Compliance - Rahmawati, Rizki; Yulianto, Agung (Universitas Negeri Semarang, 2018)
This research aimed to analyze the effect of Service Quality, Tax Penalties, Tax Amnesty and Religiosity on taxpayer’s. The population of this study are 90.485 private taxpayers who registered in KPP Pratama Semarang Candisari. The method of sample selection used in this research is Convenience Sampling by using Slovin formula as amount 100 effective Individual Taxpayers. Data collection method used is primary data through questionnaire. Data were analyzed using descriptive analysis and multiple linear regression. Based on the results of research perception of service quality has no significant effect on taxpayer compliance. Tax penalties have no significant effect on taxpayer compliance. Tax amnesty variable has a positive and significant impact on taxpayer compliance. Religiosity on taxpayer’s has a positive and significant impact on taxpayer compliance. Conclusions from this research factors that proved to influence taxpayer compliance are tax amnesty and religiosity on taxpayer’s. While the perception of service quality and tax penalties has no significant effect on taxpayer compliance. Further research is expected to change the object of research into corporate taxpayers and add other variables outside which are studied by the author